Peran Profitabilitas: Environmental, Social, dan Governance Disclosure terhadap Nilai Perusahaan - Dinda Yunita Utami; Zaky Machmuddah (Jurnal Akuntansi dan Keuangan, 2026)
This study aims to examine the moderating role of profitability in the influence of environmental, social, and governance (ESG) disclosures on firm value. The study sample consists of 66 Indonesian companies listed on the Indonesia Stock Exchange (IDX) with ESG data available in the Bloomberg database, with a total of 264 company-year observations selected using a purposive sampling method. ESG and profitability measurements were conducted in the current year (2020–2023), while firm value was evaluated in the following year (2021–2024). Multiple linear regression and Moderated Regression Analysis (MRA) were used as analytical tools. This study found mixed results: environmental disclosure had no significant effect, social disclosure had a significant positive effect, and governance disclosure had a significant negative effect on firm value. Furthermore, profitability did not moderate the effect of environmental disclosure, but weakened the effect of social disclosure and strengthened the effect of governance disclosure on firm value.